2003
DOI: 10.1007/s00125-002-1009-0
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of insulin resistance and beta-cell dysfunction to the pathophysiology of Type 2 diabetes

Abstract: The relative contributions of insulin resistance and beta-cell dysfunction to the pathophysiology of Type 2 diabetes have been debated extensively. The concept that a feedback loop governs the interaction of the insulin-sensitive tissues and the beta cell as well as the elucidation of the hyperbolic relationship between insulin sensitivity and insulin secretion explains why insulin-resistant subjects exhibit markedly increased insulin responses while those who are insulin-sensitive have low responses. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
1,399
4
41

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,829 publications
(1,474 citation statements)
references
References 175 publications
30
1,399
4
41
Order By: Relevance
“…However, direct measures (such as clamp studies) would be difficult to implement in a study of this size (n=487) given their cost, invasiveness and time requirements, which may be particularly burdensome for new mothers at 3 months postpartum. Moreover, both the IS OGTT index and insulinogenic index/HOMA-IR have been widely used in large clinical studies [19]. A second limitation is that the observational nature of these data cannot conclusively establish causality in the relationship between antepartum adiponectin and postpartum metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct measures (such as clamp studies) would be difficult to implement in a study of this size (n=487) given their cost, invasiveness and time requirements, which may be particularly burdensome for new mothers at 3 months postpartum. Moreover, both the IS OGTT index and insulinogenic index/HOMA-IR have been widely used in large clinical studies [19]. A second limitation is that the observational nature of these data cannot conclusively establish causality in the relationship between antepartum adiponectin and postpartum metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The HOMA of insulin resistance (HOMA-IR) was calculated as described by Matthews et al [17]. Beta cell function was assessed by the insulinogenic index divided by HOMA-IR (insulinogenic index/HOMA-IR) [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…It is characterized by high circulating glucose levels over a prolonged period of time which leads to long-term health complications [1]. Type 1 Diabetes (T1D) involves the autoimmune destruction of insulin-secreting β cells while Type 2 Diabetes (T2D) is linked to both a decrease of insulin release and deficient hormone action on targeted organs [2].The links among Zn 2+ , diabetes and insulin were established in the 1930s, a decade after the discovery of the hormone, when a study showed crystallized insulin contains Zn 2+ and that Zn 2+ , along with other metal ions, could reversibly trigger insulin crystallization [3]. Zinc was later demonstrated to prolong insulin action when co-injected with the hormone [4].…”
mentioning
confidence: 99%
“…It is characterized by high circulating glucose levels over a prolonged period of time which leads to long-term health complications [1]. Type 1 Diabetes (T1D) involves the autoimmune destruction of insulin-secreting β cells while Type 2 Diabetes (T2D) is linked to both a decrease of insulin release and deficient hormone action on targeted organs [2].…”
mentioning
confidence: 99%
“…During the course of the disease, pancreatic insulin production becomes decreased, and absolute insulin deficiency results (Kahn 2003). Based on these pathophysiological considerations, correcting the insulin resistance and substituting insulin is the current mainstay of diabetes therapy.…”
mentioning
confidence: 99%